ISRchain: Achieving efficient interdomain secure routing with blockchain. (May 2020) - Chen, Di; Ba, Yang; Qiu, Han; Zhu, Junhu; Wang, Qingxian
Abstract: Extensive efforts have been made for securing interdomain routing during the last two decades, but the highly centralized nature and complex management of existing security solutions impede their deployment progress. This paper presents ISRchain, a blockchain-based interdomain secure routing framework. We utilize blockchain as a distributed, tamper-proof, and traceable ledger to store the distributions of Internet number resources consistently and design a smart contract-based mechanism for route origin verification, AS adjacency attestation, and route policy compliance check. ISRchain decouples the data required for route validation from routing protocols to work independently without requiring any changes in the current interdomain routing system. We conduct extensive experiments to evaluate ISRchain's performance by simulating Internet resource allocation in the real world and show its effectiveness and efficiency by performing two case studies with BHARTI Airtel prefix hijack in 2015 and Google route leak in 2017. Experimental results demonstrate the feasibility of ISRchain for securing interdomain routing.